Least square means and heritability estimates of egg quality traits in Aseel and Kadaknath chicken - Rathi, Pallavi; Dalal, Devender Singh; Patil, Chandrashekhar Santosh (Journal of Livestock Biodiversity, 2025)
Egg quality parameters are crucial for the egg industry, as they influence grading, pricing, hatchability, and consumer preferences. To improve these traits, the poultry breeding industry is placing greater emphasis on genetic selection. Current study was undertaken to estimate the effect of non-genetic factors and estimation of genetic parameters of egg quality traits in two important Indian breeds Aseel and Kadaknath. Different parameters of external and internal egg quality were measured. Mean values for external characters of Aseel eggs viz., egg weight, shape index, albumen index, yolk index, shell weight and shell percentage were 44.76 g, 75.61%, 0.06%, 0.43%, 3.03 g and 8.8%, respectively and corresponding values for Kadaknath eggs were 40.54 g, 74.42%, 0.06% , 0.44%, 3.69 g and 10.67%, respectively. Yolk-Albumen Ratio, Haugh Unit were 0.71 and 72.42 for Aseel eggs and 0.71 and 72.47 for Kadaknath eggs, respectively. Heritability estimates for egg quality traits in both Aseel and Kadaknath breeds ranged from moderate to high indicating substantial potential for improving these traits through both individual and family selection methods.